ANALISIS PEMBELAJARAN PENDIDIKAN PANCASILA DALAM PEMBENTUKAN KARAKTER MANDIRI SISWA KELAS IV - Ifani Julianti; Tustiyana Windiyani; Nur Hikmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Ifani Julianti 037120003. Analysis of Pancasila Education Learning in the Formation of Independent Character of Grade IV Students. This study aims to determine the learning of Pancasila education in the formation of independent character of grade IV students of SD Negeri Bantarkemang 2. The type of research used is Qualitative Research through Descriptive Study Approach. The results of the study indicate that Pancasila education learning in the formation of independent character of students has been implemented quite well, starting from the planning of the contents of the learning device which contains independent character values to its implementation in order to help the formation of independent character of grade IV students, although in reality there are several inhibiting factors that affect the formation of independent character of grade IV students. This proves that Pancasila education learning carried out in the classroom has been sufficient to help students become humans who behave and behave independently. Keywords: Pancasila Education, Independent CharacterIfani Julianti 037120003. Analysis of Pancasila Education Learning in the Formation of Independent Character of Grade IV Students. This study aims to determine the learning of Pancasila education in the formation of independent character of grade IV students of SD Negeri Bantarkemang 2. The type of research used is Qualitative Research through Descriptive Study Approach. The results of the study indicate that Pancasila education learning in the formation of independent character of students has been implemented quite well, starting from the planning of the contents of the learning device which contains independent character values to its implementation in order to help the formation of independent character of grade IV students, although in reality there are several inhibiting factors that affect the formation of independent character of grade IV students. This proves that Pancasila education learning carried out in the classroom has been sufficient to help students become humans who behave and behave independently.Keywords: Pancasila Education, Independent Character